Value of Lost Load: An Efficient Economic Indicator for Power Supply Security? A Literature Review - Schröder, Thomas; Kuckshinrichs, Wilhelm (Frontiers in Energy Research, 2015)
Security of electricity supply has become a fundamental requirement for well-functioning modern societies. Because of its central position in all sections of society, the present paper considers the economic consequences of a power supply interruption. The Value of Lost Load (VoLL) is a monetary indicator expressing the costs associated with an interruption of electricity supply. This paper reviews different methods for calculating VoLL, provides an overview of recently published studies, and presents suggestions to increase the explanatory power and international comparability of VoLL.